A multiple gene genealogy reveals the phylogenetic placement of Iodosphaeria tongrenensis sp. nov. in Iodosphaeriaceae (Xylariales) - Li, Qirui; Kang, Ji-Chuan; Hyde, Kevin D. (Phytotaxa, 2015)
During collections of Sordariomycetes in Guizhou Province, China, we collected Iodosphaeria tongrenensis sp. nov.. It is unique in the genus because of its ellipsoidal ascospores (18.5–22.5 × 6.5–8.5 μm) with a slimy sheath covering the whole spore, and J+, wedge-shaped, ascal apical apparatus. Iodosphaeria is a monotypic genus in Iodosphaeriaceae and phylogenetic analyses of combined LSU, ITS and SSU sequence data indicate that it is a distinct family in the order Xylariales.